Revisiting the reconstructive surgery framework: The reconstruction supermarket - Venkatramani, H; Rodrigues, JN; Sabapathy, SR (Elsevier, 2019)
Plastic and reconstructive surgeons apply a variety of techniques throughout the body with analogies having evolved to provide a conceptual framework for the selection of techniques. Well-known examples include: the reconstructive ladder with increasingly complex rungs, the reconstructive elevator where the surgeon moves directly to the most suitable reconstruction, the reconstructive toolbox, and the reconstructive triangle.1,2 Extended models have been proposed to incorporate developments such as negative pressure wound therapy, and include the extended ladder,3 the reconstructive solar system,4 and the reconstructive clockwork.